Pharmacare and Pharmatopia / Mahirah Qistina Mohd Hisham … [et al.] - Mohd Hisham, Mahirah Qistina; Md Hussin, Nur Sabiha; Zamery, Muhammad 'Izzuddin; Karuppannan, Mahmathi (Faculty of Pharmacy, 2023)
On 17th June 2023, a total of 80 students from Sekolah Kebangsaan Puncak Alam 2 participated in the "Pharmacare and Pharmatopia" program held at the Faculty of Pharmacy, UiTM Puncak Alam. The program was a collaboration between the Society of Pharmacy Students (SOPHYS), second-semester students from the Faculty of Pharmacy, and fourth-semester students from the Faculty of Health Sciences. Pfizer Malaysia and McDonald's Malaysia, as joint organizers, provided expertise, volunteers, and food to ensure the smooth running of the program.